2016
DOI: 10.1002/tox.22236
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of mRNA and microRNA expression of a human alveolar epithelial cell(A549) exposed to water and organic‐soluble extract from particulate matter (PM)2.5

Abstract: MicroRNA (miRNA) is now attracting attention as a powerful negative regulator of messenger RNA(mRNA) levels, and is implicated in the modulation of important mRNA networks involved in toxicity. In this study, we assessed the effects of particulate matter 2.5 (PM ), one of the most significant air pollutants, on miRNA and target gene expression. We exposed human alveolar epithelial cell (A549) to two types of PM [water (W-PM ) and organic (O-PM ) soluble extracts] and performed miRNA microarray analysis. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Subsequent to sampling, the PM2.5 filter was placed under an ultraviolet lamp for 30 min and cut into two equal size pieces. The W-PM2.5 and NW-PM2.5 were isolated and prepared as previously described ( 23 ). The samples were collected and stored at −80°C until later use.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to sampling, the PM2.5 filter was placed under an ultraviolet lamp for 30 min and cut into two equal size pieces. The W-PM2.5 and NW-PM2.5 were isolated and prepared as previously described ( 23 ). The samples were collected and stored at −80°C until later use.…”
Section: Methodsmentioning
confidence: 99%
“…In recent studies, Li et al (108) found that miR-1228(*) was able to inhibit apoptosis in A549 human alveolar epithelial cells exposed to fine PM. Using the same cell line, Jeong et al (84) conducted an integrative analysis of mRNA and miRNA expression of these cells exposed to aqueous and organic-soluble extracts from PM2.5. This comprehensive analysis found that a large number of miRNAs were altered (37 and 62 miRNAs for aqueous and organic extracts, respectively), which mapped to a number of pathways important for nutrient sensing, nucleic acid synthesis, DNA synthesis, and cell cycle regulation.…”
Section: Mirnas and Heavy Metalsmentioning
confidence: 99%
“…Similarly, exposure to Milan PM2.5 has been shown to alter gene expression and the production of reactive oxygen species (ROS) in human alveolar epithelia cells (A549), and suggested that DNA damage was likely to be related to changes in the cytochrome P450 (CYP) enzyme activity 11 . Analysis of microRNA and mRNA changes in A549 cells exposed to water and organic soluble extract from PM2.5 has further indicated that the predicted target genes were involved in the regulation of cell cycle 12 . A more recent study has demonstrated sex-specific candidate gene expression in response to PM10 exposure in humans 13 .…”
Section: Introductionmentioning
confidence: 99%